Intra-Annual Course of Canopy Parameters and Phenological Patterns for a Mixed and Diverse Deciduous Forest Ecosystem Along the Altitudinal Gradients Within a Dam Reservoir Landscape - Öztürk, Melih; Biricik, Turgay; Ağlarcı, Ali Vasfi (MDPI AG, 2025)
Within a dam reservoir landscape in the Western Black Sea Region of Türkiye, a dense young-mature stand composed diversely of oriental beeches, European hornbeams, sessile oaks, and silver lindens was chosen as a study field to analyze canopy parameters and to determine phenological patterns along the altitudinal gradients. Referring to the air-soil temperature and precipitation data, intra-annual eco-physiological characteristics of that stand tree canopies, were aimed to be determined regarding those altitudinal gradients. For each of the 10 altitudinal gradients, the mixed deciduous stand canopy physiological characteristics were analyzed by hemispherical photographing. Canopy parameters were acquired from those digital hemispherical photographs, which were confirmed with secondary LAI data from the LAI-2200C. Leaf Area Index, Light Transmission, Canopy Openness, and Gap Fraction were obtained during a total of 21 study field visits throughout the monitoring year. Beginning from a theoretical leafless stage with 0.51 m2 m−2, average LAI increased to 0.89 m2 m−2 during budburst stage, and then gradually up to 3.60 m2 m−2 during climax leaf period, and then to 1.38 m2 m−2 during senescence period, and gradually down to 0.50 m2 m−2 during the next theoretical leafless stage. However, average LT (64%, 61%, 9%, 36%, 74%), CO (65%, 62%, 9%, 37%, 75%), and GF (18%, 14%, 1%, 8%, 14%) followed opposite patterns. Though no apparent trend was valid for those canopy parameters from the lowest to the highest altitudinal gradient, their obvious intra-annual patterns emerged as compatible with the annual air-soil temperature data course.
Keywords: Air-Soil Temperature; landscape ecology; Tree Eco-Physiology; QH301-705.5; elevation zones; Pr & Uuml; K & Ouml; Landscape Ecology; Tree Diversity; Kirazl & Imath; Lai; LAI; air-soil temperature; Dam Watershed; tree diversity; tree eco-physiology; Elevation Zones; Biology (General)